Dari Konvergensi ke Aksi Nyata: Implementasi Program KKN Terpadu untuk Penguatan Empat Dimensi Ketahanan Desa - Riskal Danang setiawan; Sri Yuliana; Mohamad Makrus (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Community Service Program (KKN) is one of the forms of community service carried out by university students. The purpose of KKN activities is to apply the knowledge and skills possessed by students in helping to solve problems faced by the community in the KKN area. Simpang Rimba Village, located in Simpang Rimba District, is one of the locations where KKN is implemented by students. The focus of KKN activities in Simpang Rimba Village is on four main aspects: Legal Empowerment, Economic Empowerment, Food Security, and Creative Economy. The method used in this research is observation and field study, conducted directly on site, and categorized as descriptive qualitative research. The results of the KKN implementation in Simpang Rimba Village show that the programs carried out can improve the knowledge and skills of the local community. Furthermore, KKN activities can also foster leadership, independence, and student awareness of the issues faced by the community.